(untitled) (Majalah Kedokteran Bandung, 2023)
Sepsis is a severe medical condition characterized by organ dysfunctions resulting from the body’s response to an infection. Septic shock is a complication of sepsis that involves circulatory, cellular, and metabolic disturbances. The body’s response to infection is typically marked by an increase in neutrophils and a decrease in lymphocytes, leading to increased Neutrophil Lymphocyte Ratio (NLR). This study aimed to investigate the differences in NLR between sepsis and septic shock patients treated at Dr. H. Abdul Moeloek Provincial Hospital, Lampung, Indonesia. This study utilized a comparative analytic study approach with a cross sectional design. A total of 96 sepsis patients who met the inclusion and exclusion criteria treated during the period January 2018 - December 2020 at Dr. H. Abdul Moeloek Provincial Hospital, Lampung, Indonesia, were included in this study. The study found that most of sepsis patients showed an increase in neutrophils (89.58%), a decrease in lymphocytes (94.79%), and elevated NLR values (87.5%). The mean NLR value of septic shock patients (20.10±5.89) was significantly higher than that of sepsis patients (18.01±1.35) (p=0.025). It indicates that the NLR value increases significantly in patients who develop septic shock compared to those with sepsis alone. The findings suggest that NLR could be a potential biomarker for septic shock diagnosis. However, the effectiveness of NLR in predicting the severity of sepsis and determining the risk of mortality in these patients still needs to be examined by conducting studies that involve a larger sample size.